(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Eye care in intensive care units is crucial to avoid eye problems associated with infections, use of medications, effect of mechanical ventilators, and patient position. Indeed, there is no specific guideline or protocols use in eye care in Iraqi intensive care units, so the study focused on nurses to assess their knowledge regarding evidence-based practice toward eye care. Objectives: The objective of this study was to assess nurses’ knowledge regarding evidence-based practice toward eye care in intensive care units, and to find out relationships between their demographics and total knowledge. Method: A descriptive study using a purposive sample (non-probability) was used to survey 30 nurses who met the sampling criteria in two teaching hospitals in the south of Iraq to assess their knowledge regarding eye care. A valid and reliable tool was used after getting the permission from the copyright holder. Results: More than one-third of study sample were (22-26) years old they account (40%). Majority of them were male (56.7%), and (53.3%) of the study sample had bachelor’s degree in nursing. Regarding years of experience half of the study sample had more than five years of experience in intensive care units. Majority of the study sample (63.3%) has no participation in training courses about eye care and (83.3%) was day shift of work. The total mean of score of nurses’ knowledge was poor (0.33). Conclusion: There is a need to conduct training courses for nurses who work in intensive care units about eye care based on standard as the results in this study indicated that there is a significance association between, nurses’ knowledge and participation in training course, about eye care.